Synthesis of Nitrogen Heterocycles by a C–C Cross-Coupling/Cycloisomerization Strategy - Langer, Peter (Synlett, 2022)
The present article presents a personalized Account on the synthesis of nitrogen heterocycles by combination of regioselective Pd-catalyzed cross-coupling reactions of polyhalogenated heterocycles, i.e., Suzuki–Miyaura and Sonogashira reactions, with acid-mediated cycloisomerization reactions. In many cases, the products constitute new heterocyclic core structures and show interesting optical and electronic properties.1 Introduction2 Acridines3 Phenathridines4 Azapyrenes5 Thienoquinolines6 Pyrrolonaphthyridines7 6-Aza-ullazines8 Conclusions
Keywords: catalysis; cross-coupling; cycloisomerization; heterocycles; palladium; regioselectivity